A developmental and clinical perspective of rhythmic interpersonal coordination: From mimicry toward the interconnection of minds. Issue 4 (November 2016) - Xavier, Jean; Magnat, Julien; Sherman, Alain; Gauthier, Soizic; Cohen, David; Chaby, Laurence
Highlights: Synchrony leads, from an experience of similarity, to the interconnexion of minds. Through imitation, rhythmic interpersonal coordination is precursor to TOM and empathy. DCD are characterized by childhood deficits in rhythmic interpersonal coordination. Impairments in synchrony have an impact on an emotional and socio-interactional level. Abstract: Imitation plays a critical role in the development of intersubjectivity and serves as a prerequisite for understanding the emotions and intentions of others. In our review, we consider spontaneous motor imitation between children and their peers as a developmental process involving repetition and perspective-taking as well as flexibility and reciprocity. During childhood, this playful dynamic challenges developing visuospatial abilities and requires temporal coordination between partners. As such, we address synchrony as form of communication and social signal per se, that leads, from an experience of similarity, to the interconnection of minds. In this way, we argue that, from a developmental perspective, rhythmic interpersonal coordination through childhood imitative interactions serves as a precursor to higher- level social and cognitive abilities, such as theory of mind (TOM) and empathy. Finally, to clinically illustrate our idea, we focus on developmental coordination disorder (DCD), a condition characterized not only by learning difficulties, but also childhood deficits in motor imitation. We address the challenges faced by these children on an emotional and socio-interactional level through the perspective of their impairments in intra- and interpersonal synchrony.